Maksimalkan Potensi Desain Dalam Aplikasi Canva: Menyajikan Ide Kreatif Dengan Desain Yang Menginspirasi - Siti Sahariah; Ilmi Rahma Fadila; Salsabela Oktanur Ichwana; Selpi Aulia; Ana Noor Andriana; Annisa Wahyuni Arsyad (Jurnal Pengabdian Masyarakat Manage, 2024)
Abstract:Expressing creative ideas through graphic design is one of the skills that we must acquire today because it is useful not only in everyday life but also in the work environment. However, there are some people who are currently unable to create graphic designs. This could be due to a lack of basic knowledge about graphic design and how to use easy-to-use applications. Therefore, the purpose of community service in this Zoom webinar is to increase the enthusiasm of the community in developing their creativity, allowing them to channel their creative ideas and express themselves through graphic design using the Canva application. The methods used in this community service activity are monological and interactive. The result of this activity is that participants get a new perspective in fostering the spirit of creativity for innovation in the company using the Canva application, this shows a positive response from the participants. These results can be seen in the evaluation diagram which shows a positive response rate of 71.4%.